Effects of Different Anesthetic Agents on Surgical Site Hemorrhage During Circumcision - Karasu, Derya; Yilmaz, Canan; Ozgunay, Seyda Efsun; Karaduman, Isra; Ozer, Demet; Kaya, Mete (Urology Journal, 2018)
Purpose: To investigate the effects of ketamine+midazolam and propofol+sevoflurane anesthesia on surgical site hemorrhage during circumcision procedures. Materials and Methods: The boys undergoing circumcision surgery were included in the study. The patients were divided into two groups. In Group 1 (n = 50), 0.01 mg/kg midazolam and 2 mg/kg IV ketamine were administered. In Group 2 (n = 50), 1 ?g/kg fentanyl, 1 mg/kg lidocaine 2%, and 2–3 mg/kg IV propofol were administered, and patency of airway was ensured with a laryngeal mask airway. The intraoperative bleeding scale was recorded during the procedure to evaluate surgical site bleeding. Hemorrhage was checked for the first three hours using the postoperative bleeding scale to follow the amount of hemorrhage. Results: Intraoperative bleeding scores were significantly higher in Group 1 as compared to Group 2. However, there was no significant difference between the groups regarding frequency of postoperative hemorrhage. The mean blood pressure values measured at 5th, 10th, 15th minutes and recovery room were significantly higher in Group 1. Conclusion: The intraoperative bleeding scores were significantly higher with ketamine+midazolam compared to propofol+sevoflurane. On the other hand this hemorrhage can be controlled easily with appropriate hemostasis, and the amount of blood loss was not clinically significant. We think that our study makes a positive contribution to the literature about the effects of anesthetics on the surgical site bleeding during circumcision. Clinical Trials Registration: ACTRN12616000189426